Perbandingan Kinerja Keuangan Sebelum dan Sesudah Merger dan Akuisisi pada Perusahaan Non-Bank yang Tercatat di BEI Periode 2015 - Fitriah Fatimah Amatilah; Mochamad Edman Syarief; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
Merger and Acquisition is one of firm’s effort to maintain and develop life of firm. Research analyze the difference of the firm’s financial performance pre and post merger and acquisition. The sample uses companies listed on the Indonesia Stock Exchange (IDX) and conducted mergers and acquisitions in 2015. The sample consists of 3 acquirer companies that meet the criteria. This study uses a different test Wilcoxon Signed Ranks Test. The results show that of 5 financial ratios, namely, leverage ratio as measured by Debt to Equity Ratio, activity ratio as measured by Total Asset Turnover, profitability ratio as measured by Return On Assets, Return On Equity, and Operating Profit Margin, and market ratios as measured by Price to Book Value experienced significant changes between before and after the company carried out mergers and acquisitions, except for the liquidity ratio measured by Current Ratio which did not change between before and after mergers and acquisitions.